Numerical analysis of magnetohydrodynamic mixed convection and entropy generation in a curvelinear lid-driven cavity with carbon nanotubes and an adiabatic cylinder - Mohammed Azeez Alomari; Qusay H. Al-Salami; Farah Q. A. Alyousuf; Faris Alqurashi; Mujtaba A. Flayyih (International Journal of Thermofluids)
Mixed convection convection is a vital subject and it is beneficial in many engineering applications. The current paper addresses this subject with a novel geometry and very vital variables including magnetohydrodynamic influences on the forced/free convection as well as the reproduction of irreversibilities in an enclosure filled with water/carbon nanotubes (CNT) and a nonadiabatic cylinder. The top wall is split from the middle and moves in different directions to drive the isotherms which are generated from the bottom wall and cold from the vertical surfaces. The numerical analysis was carried out using finite element method; the variables are Reynolds number (40–200), Richardson number (0.01–10), Hartmann number (0–62), inclined magnetohydrodynamic angle (0–60), volume concentration (0–0.08) while Prandtl number has kept constant at 6.2. The results show that the transformation of heat, as well as the fluid flow, are largely influenced by the change of variables, where increasing Reynolds number, Richardson number enhances heat and increases the flow circulation. Furthermore, heat transfer enhances by 57 % when increasing Ri from 0.1 to 10 at Re=41 and this enhancement increases to 62.5 % at Re = 200. Furthermore, increasing the concentration of the carbon nanotube can cause heat transfer but decrease the circulation of the fluid. In contrast, the transfer of heat as well as the flow streams are remarkably decreased with the increase of the Hartmann at zero inclination angle; however, the value of the Nusselt average increases with the increase of the inclination angle. Moreover, the value of Nusselt average decreses by 34.7 % when increasing Ha from 0 to 62 at Re = 200. Furthermore, the total entropy generation increases as Richardson number, Reynolds number, and volume concentration increase; in contrast, detraction with the rise of the MHD.